Melt-spun Fe–Sb intermetallic alloy anode for performance enhanced sodium-ion batteries - Edison, Eldho (2020)
Owing to the high theoretical sodiation capacities, intermetallic alloy anodes have attracted considerable interest as electrodes for next-generation sodium-ion batteries (SIBs). Here, we demonstrate the fabrication of intermetallic Fe–Sb alloy anode for SIBs via a high-throughput and industrially viable melt-spinning process. The earth-abundant and low-cost Fe–Sb-based alloy anode exhibits excellent cycling stability with nearly 466 mAh g–1 sodiation capacity at a specific current of 50 mA g–1 with 95% capacity retention after 80 cycles. Moreover, the alloy anode displayed outstanding rate performance with ∼300 mAh g–1 sodiation capacity at 1 A g–1. The crystalline features of the melt-spun fibers aid in the exceptional electrochemical performance of the alloy anode. Further, the feasibility of the alloy anode for real-life applications was demonstrated in a sodium-ion full-cell configuration which could deliver a sodiation capacity of over 300 mAh g–1 (based on anode) at 50 mA g–1 with more than 99% Coulombic efficiency. The results further exhort the prospects of melt-spun alloy anodes to realize fully functional sodium-ion batteries.